Mpox in people with advanced HIV infection: a global case series. Issue 10380 (18th March 2023) - Mitjà, Oriol; Alemany, Andrea; Marks, Michael; Lezama Mora, Jezer I; Rodríguez-Aldama, Juan Carlos; Torres Silva, Mayara Secco; Corral Herrera, Ever Arturo; Crabtree-Ramirez, Brenda; Blanco, José Luis; Girometti, Nicolo; Mazzotta, Valentina; Hazra, Aniruddha; et al.
Summary: Background: People living with HIV have accounted for 38–50% of those affected in the 2022 multicountry mpox outbreak. Most reported cases were in people who had high CD4 cell counts and similar outcomes to those without HIV. Emerging data suggest worse clinical outcomes and higher mortality in people with more advanced HIV. We describe the clinical characteristics and outcomes of mpox in a cohort of people with HIV and low CD4 cell counts (CD4 <350 cells per mm 3 ). Methods: A network of clinicians from 19 countries provided data of confirmed mpox cases between May 11, 2022, and Jan 18, 2023, in people with HIV infection. Contributing centres completed deidentified structured case report sheets to include variables of interest relevant to people living with HIV and to capture more severe outcomes. We restricted this series to include only adults older than 18 years living with HIV and with a CD4 cell count of less than 350 cells per mm 3 or, in settings where a CD4 count was not always routinely available, an HIV infection clinically classified as US Centers for Disease Control and Prevention stage C. We describe their clinical presentation, complications, and causes of death. Analyses were descriptive. Findings: We included data of 382 cases: 367 cisgender men, four cisgender women, and ten transgender women. The median age of individuals included was 35 (IQR 30–43) years. At mpox diagnosis, 349 (91%) individuals were known to be living with HIV; 228 (65%) of 349 adherent to antiretroviral therapy (ART); 32 (8%) of 382 had a concurrent opportunistic illness. The median CD4 cell count was 211 (IQR 117–291) cells per mm 3, with 85 (22%) individuals with CD4 cell counts of less than 100 cells per mm 3 and 94 (25%) with 100–200 cells per mm 3 . Overall, 193 (51%) of 382 had undetectable viral load. Severe complications were more common in people with a CD4 cell count of less than 100 cells per mm 3 than in those with more than 300 cells per mm 3, including necrotising skin lesions (54% vs 7%), lung involvement (29% vs 0%) occasionally with nodules, and secondary infections and sepsis (44% vs 9%). Overall, 107 (28%) of 382 were hospitalised, of whom 27 (25%) died. All deaths occurred in people with CD4 counts of less than 200 cells per mm 3 . Among people with CD4 counts of less than 200 cells per mm 3, more deaths occurred in those with high HIV viral load. An immune reconstitution inflammatory syndrome to mpox was suspected in 21 (25%) of 85 people initiated or re-initiated on ART, of whom 12 (57%) of 21 died. 62 (16%) of 382 received tecovirimat and seven (2%) received cidofovir or brincidofovir. Three individuals had laboratory confirmation of tecovirimat resistance. Interpretation: A severe necrotising form of mpox in the context of advanced immunosuppression appears to behave like an AIDS-defining condition, with a high prevalence of fulminant dermatological and systemic manifestations and death. Funding: None.